The Effects of Leadership, Competence, and Organizational Culture on Employee Performance Mediated By Employee Satisfaction - Triono Nugroho; Anita Erari; Sandra Sukmaning Adji (Britain International for Academic Research (BIAR) Publisher, 2021)
Improving employee performance is an important and mandatory thing to be realized, especially in local government organizations. This study aims to determine and analyze the influence of leadership, competence and organizational culture on employee performance mediated by employee job satisfaction. This research was conducted on the employees of the Department of Investment and One Stop Services (DPMPTSP) of Yapen Islands Regency with a population of 32 employees, where all employees were used as samples. The independent variables in this study are leadership, competence and organizational culture, while the dependent variable is employee performance mediated by job satisfaction. The research data was obtained by distributing questionnaires and then measuring the variables using a Likert scale. Furthermore, the data were analyzed using a Structural Equation Model (SEM) approach based on Partial Least Square (PLS), namely Smart-PLS version 3. The results showed that: 1) leadership had no significant effect on employee performance, but had a significant effect on job satisfaction; 2) competence has a significant effect on employee performance, but is not significant in influencing job satisfaction; 3) organizational culture has a significant effect on employee performance and job satisfaction; 4) job satisfaction has a significant effect on employee performance; 5) job satisfaction can mediate the relationship of leadership to employee performance, but cannot mediate the relationship of competence and organizational culture to employee performance.